Implementasi Kebijakan Pekerja Harian Lepas Disabilitas Di Kepolisian Resor Kota Tangerang Selatan - Adha Agung Saputro; Abdullah Qiqi Asmara (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
Empowering people with disabilities The Police Resort (Polres) and the South Tangerang City Social Service (Dinsos) have built synergy to empower the abilities of people with disabilities. However, in practice the implementation of casual daily workers with disabilities at the Polres is still experiencing significant obstacles. The purpose of this research is to analyze the implementation of disability casual daily workers at the Tangerang City Resort Police using a descriptive method with a qualitative approach based on the implementation model theory according to Van Meter and Van Horn, several conclusions can be drawn: 1. Size and objectives in the casual workers policy program disability is very good and helps people with disabilities to get decent jobs. 2. The resources that the Polres have in carrying out policies in terms of human resources are inadequate in terms of numbers. 3. the characteristics of the implementing agency in carrying out the policy already have a good relationship seen from the existence of inter-agency support in implementing the policy. 4. The communication carried out between the South Tangerang Police and the South Tangerang City Social Service has not gone well, this can be seen in the absence of further routine supervision. 5. Attitudes or tendencies, in this case the attitude of the South Tangerang Police in implementing the policy has been going well. 6. The economic, social and political environment has not yet affected the implementing agencies due to the absence of special encouragement from the South Tangerang Police and the Social Service.